(untitled) (Development Service Industry Management, 2024)
Ensuring the sustainable development of tourism in the country through effective state regulation and strategic management is of great importance in modern conditions. In the context of negative trends in the field of tourism, it is important to emphasize the need to implement effective mechanisms that will help overcome these challenges. The preservation of unique natural and cultural resources, as well as the improvement of the country’s positive tourist image on the international market, are especially relevant. The development of tourism requires the creation of favorable conditions for the formation of a competitive national tourist product, which can ensure not only economic, but also socio-cultural development. Therefore, the relevance of the study lies in the need to develop and implement strategies for the development of sustainable tourism at the level of local communities, in particular, in the Satanivska United Territorial Community of Khmelnytskyi Region. In the conditions of growing attention to environmental issues, as well as increasing interest in tourism as an important segment of the economy, the study and effective use of tourist and recreational resources is of great importance. Analysis and assessment of available resources, identification of their potential and problems will allow to develop specific measures to improve the tourist infrastructure, attract investments and create a favorable environment for the development of tourism in the region. The article is devoted to the study of the current state and prospects for the development of sustainable tourism in the Satanivska United Territorial Community of Khmelnytskyi Region. The history of the territorial community was reviewed, the tourist and recreational resources available in it were analyzed, and the peculiarities of their use were investigated. The activity of institutions and entities regulating the field of tourism, the dynamics of the development of tourist and recreational facilities, and the impact of tourism on the environment of the community were analyzed. Based on the results of the SWOT/TOWS analysis of the community’s tourism and recreation sphere, the problems and prospects of implementing the strategy of sustainable tourism development are highlighted, as well as recommendations for the development of sustainable tourism and the promotion of the community’s tourism brand.